Penggunaan bahasa kias dalam komunikasi sosial oleh masyarakat saluan di Kabupaten Banggai - Rafii, Muh (Universitas Lampung, 2023)
The use of figurative language with the aim of strengthening the message conveyed, which is embedded in social communication between people in one community in the context of daily communication, is a unique thing to explore. By using a qualitative approach, this study aims to find out the use of figurative language and the figurative meaning used. The data in this study was in the form of words, utterances or spoken sentences that contain figures of speech in everyday communication. The method used in data collection was the method of observing and recording techniques. The data obtained was then analyzed by selecting, sorting, classifying data, reading, studying and removing unnecessary data. The results of the study show that in social communication, the Saluan people in Batu Itam Village use a lot of figures of speech in the form of simile, namely comparing one object to another. Other objects that are used as comparisons are substitute objects that represent actual objects or allude to other objects but are not pronounced. The Saluan people also use visible objects to become figurative components.Keywords: figurative language, social communication, simile